The speech of children and adolescents in special testimony: violence entangled in the courtroom - Mariana Ribeiro Melo; Laura Cristina Eiras Coelho Soares (Estudos de Psicologia (Campinas))
Abstract Objective The present article aims to comprehend how child sexual abuse and the testimony of victims are approached in legal proceedings utilizing the Special Testimony technique. Method To achieve the objective, the authors examined judicial decisions published by the Court of Justice of Minas Gerais. Through documentary analysis, 21 sentences were collected, and content analysis was employed, integrating the data with the literature on Special Testimony and the field of Legal Social Psychology. Results The observations encompassed the child’s testimony as the sole piece of evidence, the influence of the media on legislative and judicial processes, the significance of documents and positions from Psychology in the courts, as well as the noteworthy manner in which the child articulates their speech. Conclusion Psychology is called upon to formulate positions and guide practices while carefully considering the limits and objectives of its intervention.